2017
DOI: 10.1080/21645515.2017.1403695
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists as vaccinators: An analysis of their experiences and perceptions of their new role

Abstract: These findings suggest that pharmacists are accepting of their role as vaccinators but more research is needed to examine impact on workload and pharmacist knowledge and perceptions of injection-related pain and fear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…It is not known whether newer practitioners were more interested in embracing expanded scope of practice or if they felt more pressure to obtain immunization training to obtain and maintain professional employment. This was observed in a recent qualitative study, in which respondents felt compelled to become certified and provide immunizations for employment 46…”
Section: Discussionmentioning
confidence: 79%
“…It is not known whether newer practitioners were more interested in embracing expanded scope of practice or if they felt more pressure to obtain immunization training to obtain and maintain professional employment. This was observed in a recent qualitative study, in which respondents felt compelled to become certified and provide immunizations for employment 46…”
Section: Discussionmentioning
confidence: 79%
“…Similarly, Canadian pharmacists have reported that providing immunization services allows them to improve the relationships they have with their patients and to get to know their patients more. 22 The participants in this study reported that immunization in community pharmacies would be cost-saving for patients and would, therefore, reflect the active role of the pharmacist towards the community. Although community pharmacybased influenza vaccination is associated with reduced health-related costs, 23 little is known about the economic impact of allowing pharmacists to provide the influenza vaccine to patients in Jordan.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, Canadian pharmacists have reported that providing immunization services allows them to improve the relationships they have with their patients and to get to know their patients more. 22 …”
Section: Discussionmentioning
confidence: 99%
“…This common challenge was reported in many countries such as Canada and Australia, where a erce averseness from the physicians toward permitting pharmacists to administer vaccinations. The reasons behind this opposition and lack of support were reasoned that pharmacists were not adequately or effectively trained to do vaccination or to manage adverse effects following vaccine administration [17][18][19].…”
Section: Resultsmentioning
confidence: 99%